2015
DOI: 10.4284/0038-4038-2012.301
|View full text |Cite
|
Sign up to set email alerts
|

The effects of competition on the nature of cheating behavior

Abstract: Competition among individuals comes in a variety of forms: for mates, for resources, and for prestige and recognition. Such competitive pressure can lead individuals to engage in unethical behavior in an effort to get ahead. There are several forms of cheating in which individuals may engage to improve their own outcome: they may lie about their own performance in a task and they may lie about others performance in a task. Our research is the first to examine how competition affects each of these two types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 23 publications
4
42
2
Order By: Relevance
“…This contrasts with Rigdon and D'Esterre (2015) who found that people lie less when reporting the performance of another subject than when reporting their own performance. However, our results become consistent with theirs when we remove the experimenter's scrutiny (as in their study), as in this condition subjects report higher numbers for themselves than for their opponent in absolute terms.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…This contrasts with Rigdon and D'Esterre (2015) who found that people lie less when reporting the performance of another subject than when reporting their own performance. However, our results become consistent with theirs when we remove the experimenter's scrutiny (as in their study), as in this condition subjects report higher numbers for themselves than for their opponent in absolute terms.…”
Section: Discussioncontrasting
confidence: 75%
“…However, Rigdon and D'Esterre (2015) have found evidence that individuals misreport more their own performance than the performance of another person, in both competitive and noncompetitive settings. Similarly, we conjecture that in our experiment subjects are more likely to overreport their own number than underreport their opponent's number, because harming directly another person may be perceived as aggressive.…”
Section: Behavioral Conjecturesmentioning
confidence: 99%
“…In all treatments the matrix search task was completed by participants in a tournament setting as described above (Rigdon and D'Esterre ). In order to examine the impact of priming competitiveness on cheating in a tournament setting, three conditions vary the scrambled sentence task: N one , N eutral and C ompetitive .…”
Section: Design and Methodsmentioning
confidence: 99%
“…Rigdon and D'Esterre () report results on how competition impacts both the level and nature of cheating. Prior to completing the matrix search task, participants were randomly and anonymously matched with one other person: only the person with the highest reported score would receive the piece‐rate payment for the task; the other would receive zero.…”
Section: Related Researchmentioning
confidence: 99%
See 1 more Smart Citation